STUDI LITERATUR PENGEMBANGAN FORMULASI FREEZE-DRYING NANOPARTIKEL LIPID RIFAMPISIN TERMODIFIKASI KONJUGAT KITOSAN-ACEMANNAN - Salsabila, Athaya
To treat intracellular infection of Staphylococcus aureus, a nanostructured lipid carrier (NLC) loaded with rifampicin can enhance the penetration of rifampicin into cells. Freeze-drying is an effective method to preserve the stability of nanoparticle for long-term storage. This research aimed to obtain the optimum freeze-drying formulation and optimum freeze-drying process based on literature research using NLC loaded with rifampicin formula that has been optimized in previous research. Formulation optimization was done by comparing the increasing of nanoparticle size towards various cryoprotectants and its concentration. Cryoprotectant was chosen based on the value of Sf/Si ratio (nanoparticle size after/before freeze-drying) and its compatibility towards chitosan-acemannan conjugate. The researcher proposed the combination of trehalose 2%-20% w/v and sucrose 2%-20% w/v as cryoprotectant that will be used in freezedrying formulation, with the value of Sf/Si nearly 1 and good compatibility towards chitosanacemannan conjugate. Freeze-drying process optimization was done by literature research in terms of the influence of freezing method, slow and rapid freezing, towards the increase of nanoparticle size and rifampicin stability. The selected freezing method should exert a lower increase of nanoparticle size yet still preserve the stability of rifampicin. The researcher proposed a slow freezing method to be used, which is -70 oC until -40 oC for 4-12 hr in the freeze-drying process of NLC loaded with rifampicin. Lyophilized NLC loaded with rifampicin have a size of around 300 nm with a low polydispersity index. Zeta potential has a positive value of 1.66 ± 1.39 mV with encapsulation efficiency approaching 93%